2007
DOI: 10.1016/j.nimb.2007.04.246
|View full text |Cite
|
Sign up to set email alerts
|

High-yield D–T neutron generator

Abstract: A high-yield D-T neutron generator has been developed for neutron interrogation in homeland security applications such as cargo screening. The generator has been designed as a sealed tube with a performance goal of producing 5·10 11 n/s over a long lifetime. The key generator components developed are a radio-frequency (RF) driven ion source and a beam-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 9 publications
2
24
0
Order By: Relevance
“…The required beam current density was extracted at a moderate microwave power of 400 W at the desired low gas pressures. This compares favorably with the power requirements (∼ 1500 W) of a previously developed RF-driven source [9,1]. It was further found that the use of an aluminumnitride vacuum window led to an approximately 30% higher extracted beam current than measured for a quartz window.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…The required beam current density was extracted at a moderate microwave power of 400 W at the desired low gas pressures. This compares favorably with the power requirements (∼ 1500 W) of a previously developed RF-driven source [9,1]. It was further found that the use of an aluminumnitride vacuum window led to an approximately 30% higher extracted beam current than measured for a quartz window.…”
Section: Resultssupporting
confidence: 57%
“…1) was developed at the Lawrence Berkeley National Laboratory to address the needs of homeland security, non-proliferation, and nuclear safeguards applications. This generator was designed to produce high neutron yields, exceeding 5 · 10 11 n/s in D-T operation and reaching about ∼ 1·10 10 n/s in D-D operation [1] when operating at 100 kV acceleration voltage and a 100 mA beam current impinging on a beam-loaded neutron production target. A V-shaped target geometry in combination with beam extraction from the ion source through a large 60 · 6 mm 2 slit serves to distribute the beam current and heat load over a larger area for better cooling of the target surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Titanium coating on copper can also be used for nuclear waste assay applications in which deuterium or tritium can be stored in titanium (Csikai 1987). When bombarded with accelerated deuterium ions, the trapped gases in the coating can undergo fusion and the high energy neutrons thus emitted (Ludewigt et al 2007) may be utilized to assess the amount of fissile material present in the nuclear waste from a power plant. The heat generated during the process is conducted away by the water cooled copper substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Neutron generators that utilize rf-driven plasma ion sources have been developed at the Lawrence Berkeley National Laboratory (LBNL) [1][2][3][4][5][6]. These neutron generators are useful in the interrogation of cargo or luggage containers, which may contain explosives, contraband, or special nuclear materials.…”
Section: Introductionmentioning
confidence: 99%